Conisbrough Court Rolls - University of Sheffield - Humanities Research Institute (2021)
"Conisbrough was one of the important royal manors of Yorkshire. Its Court Rolls provide us with a unique account of the working lives and relationships of its inhabitants. The Rolls survive in large measure across eight centuries. This project aims to show what can be done with such remarkable documents. Through it, you can discover the historic workings of a manor and learn more about Conisbrough and how its past has contributed to its present." [self-descripton]